Pengaruh gaya kepemimpinan, disiplin kerja,Dan pemberian kompensasi terhadap Kinerja karyawan di SMK Negeri 2 Salatiga - Wijatmiko, Adhistana Galyh; , Muzakar Isa, SE., M.Si (2016)
This study aimed to analyze the influence of leadership style, work discipline, and compensation for the performance of employees in SMK NEGERI 2 SALATIGA. The method used for sampling in this research using random sampling techniques, data types and sources of data used in this study use primary data obtained from the respondents' answers in the form of charging kwesioner and interviews of employees SMK NEGERI 2 SALATIGA. A total of 100 respondents were taken as the sample. From this research it is known that the style of leadership, work discipline, and compensation payments have significant influence on the performance of employees in SMK NEGERI 2 SALATIGA either partially or jointly. Compensating the most influential variables on the performance of employees is shown by the greatest results 5.586. The influence of leadership style, work discipline, and the compensation together significantly affect the performance of the employee indicated by the F test results of 43.571, while the variation of the employee's performance is explained by the variable influence of leadership style, work discipline, and the provision of compensation for while the remaining 57.7% is influenced by other variables. From the above data it can be concluded that the Compensation variable most dominant influence on the performance of employees of SMK NEGERI 2 SALATIGA.